2019
DOI: 10.1371/journal.pone.0221622
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal pattern distributions in racehorse saddles using infrared thermography

Abstract: The impact of a rider’s and saddle’s mass on saddle thermal pattern distribution was evaluated using infrared thermography (IRT). Eighteen racehorses were ridden by four riders with their own saddle. Images of the saddle panels were captured at each of six thermographic examinations. On each image, six regions of interest (ROIs) were marked on the saddle panels. The mean temperature for each ROI was extracted. To evaluate the influence of load on saddle fit, 4 indicators were used: ΔT max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…However, in horses, only a few studies exist that evaluated IRT usefulness during training monitoring. Most of this research was performed to identify the source of lameness [29,30], as well as the influence of the rider and saddle mass on the saddle fit [31]. One publication discussed thermographic horse and rider matching during leisure riding [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, in horses, only a few studies exist that evaluated IRT usefulness during training monitoring. Most of this research was performed to identify the source of lameness [29,30], as well as the influence of the rider and saddle mass on the saddle fit [31]. One publication discussed thermographic horse and rider matching during leisure riding [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors speculate that many imaging approaches applied successfully in equine veterinary medicine [1,25] can also be used for donkey IRT imaging, subject to the visualization conditions presented here. The IRT may become a useful diagnosis tool in donkeys, particularly in the field of orthopedics [5][6][7]14] or effort assessment [21,22,24], but even in the field of animal welfare [2,18,33]. Given the increase in general interest in donkeys, as milk producers, companion animals [33], and working animals under a saddle and in a harness [47], the new noninvasive imaging approaches in donkeys are in demand.…”
Section: Similarities In Thermal Patterns Of Horses and Donkeysmentioning
confidence: 99%
“…Infrared radiation is often presented as a thermogram, which is an image where the color gradient corresponds to the distribution of surface temperatures [1]. Furthermore, the relationship of temperature gradients may create specific thermal patterns, which may be used, e.g., for assessing the influence of load on saddle fit in horses [2] or the horses' response to the training [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found infrared thermography to be a valuable tool in non-invasive evaluation of saddle thermal pattern distribution (Arruda et al, 2011;Soroko et al, 2018). Soroko et al (2019) evaluated 18 racehorses that were ridden by four riders with their own saddles and concluded that infrared thermography offered a non-invasive, rapid and simple method for assessing load on thermal pattern distribution in race saddles.…”
Section: Introductionmentioning
confidence: 99%